Visible-light-induced 4CzIPN/LiBr system: a tireless electron shuttle to enable reductive deoxygenation of N-heteroaryl carbonyls. Issue 16 (15th June 2021) - Zhong, Shuai; Deng, Guo-Jun; Dai, Zhiqi; Huang, Huawen
Abstract : A mild visible-light-induced photoredox system was found to be a tireless electron shuttle to enable reductive deoxygenation of N-heteroaryl carbonyls. Abstract : Herein, we report a visible-light-induced photoredox system that enables efficient reductive deoxygenation of N-heteroaryl ketones and alcohols under mild conditions. The combinational use of 4CzIPN as photocatalyst and LiBr as additive in acidic media constitutes a tireless electron shuttle to transfer electrons from benzaldehyde to N-heteroaryl carbonyls. Mechanistically, the reduction course involves two-round sequential cascade of proton-coupled electron transfer, spin-center shift, and single-electron-transfer processes. The presented reductive deoxygenation protocol provides a mild route to pharmaceutically valuable alkyl and benzyl N-containing heteroarenes.